PEMANFAATAN SUMBER DAYA ALAM SEBAGAI MEDIA PEMBELAJARAN IPA DI SDN INPRES MAWU DALAM - Hartanti, Hartanti; Indriani, Irma; Mulyadin, Mulyadin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2024)
This study aims to explore the utilization of natural resources as science learning media at SDN Inpres Mawu Dalam, a school located in a remote area with limited access to technology. Using a qualitative descriptive approach, the research examines the implementation, challenges, and impacts of employing natural resource-based learning media. The findings reveal that natural resources such as water, plants, and stones play a significant role in enhancing students' understanding of science concepts, boosting their learning motivation, and encouraging creativity among both students and teachers. Despite these benefits, several challenges arise, including time constraints, limited resources, and unfavorable weather conditions. This study emphasizes the importance of adopting an environment-based approach as an innovative solution to improve the quality of science education, particularly in remote areas where technological access is restricted. By leveraging local resources, schools can create meaningful and engaging learning experiences that are relevant to students' daily lives.